2015
DOI: 10.1128/mcb.01172-14
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Switching of Active Promoter and Enhancer Domains Regulates Tet1 and Tet2 Expression during Cell State Transitions between Pluripotency and Differentiation

Abstract: The Tet 5-methylcytosine dioxygenases catalyze DNA demethylation by producing 5-hydroxymethylcytosine and further oxidized products. Tet1 and Tet2 are highly expressed in mouse pluripotent cells and downregulated to different extents in somatic cells, but the transcriptional mechanisms are unclear. Here we defined the promoter and enhancer domains in Tet1 and Tet2. Within a 15-kb "superenhancer" of Tet1, there are two transcription start sites (TSSs) with different activation patterns during development. A 6-k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
55
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(59 citation statements)
references
References 67 publications
1
55
0
1
Order By: Relevance
“…It was recently shown that TET1 promoter is hypermethylated and transcriptionally silenced in human non-Hodgkin B cell lymphoma (50) and in murine cell lines (51). To investigate the role of methylation modification at cg23602092 on transcription in nasal cells, we evaluated expression profiles of TET1 using qPCR analysis.…”
Section: Resultsmentioning
confidence: 99%
“…It was recently shown that TET1 promoter is hypermethylated and transcriptionally silenced in human non-Hodgkin B cell lymphoma (50) and in murine cell lines (51). To investigate the role of methylation modification at cg23602092 on transcription in nasal cells, we evaluated expression profiles of TET1 using qPCR analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Expectedly, promoter methylation that represses gene expression is detected, but DMRs in gene bodies were found to have both inverse and direct correlations with gene expression. In addition, genes may not necessarily show an expression change despite the presence of a DMR, and other hypotheses, such as alternative splicing regulation (Shukla et al, 2011), shared promoters with long noncoding RNAs (Eun et al, 2013), and regional enhancer effects (Sohni et al, 2015) should be considered. For intergenic DMRs, the enrichment of DNA-protein binding sites and motifs is suggestive of function, and the exact nature will need to be defined by future molecular testing.…”
Section: Discussionmentioning
confidence: 99%
“…Because Tet1 and Tet2 expression levels are low in EpiSCs, both genes were presumed to be silenced soon after implantation 7,20 . However, we recently showed a persistence of Tet1 expression and silencing of only Tet2 in the transition from ESCs to EpiLCs 21 .…”
mentioning
confidence: 93%